Ontological analysis of the subject area of the Algo500 digital platform - Antonov, Alexander S.; Maier, Rostislav V. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2023)
The Algo500 digital platform project is aimed at solving the problem of joint analysis of the properties of algorithms and features of supercomputer architectures. In this paper, based on the methodology of ontological analysis, concepts, models and metamodels of data are considered and proposed, approaches to the description of some concepts from the world of high-performance computing (HPC) are substantiated, new requirements for data models are established, which should ensure the fulfillment of the tasks set when creating the Algo500 platform.